Immune Responses to Inhalant Mammalian Allergens - Hentges, François; Léonard, Cathy; Arumugam, Karthik; Hilger, Christiane (Frontiers in Immunology, 2014)
In Europe and the USA at least one person in four is exposed every day to inhalant allergens of mammalian origin, a considerable number is regularly exposed for professional reasons and almost everyone is occasionally exposed to inhalant allergens from pets or domestic animals. The production of IgE to these inhalant allergens, often complicated by asthma and rhinitis, defines the atopic status. However the immune response to these allergens largely imprints the cellular immune compartment and also drives non IgE humoral immune responses in the allergic and non-allergic population. During the recent years it has become clear that IgE antibodies recognize allergens belonging to 3 protein or glycoprotein families: the secretoglobins, the lipocalins and the serum albumins. In this article we review the humoral and cellular immune responses to the major members of these families and try to define common characteristics and also distinctive features.